The Hilbert challenge - Gray, Jeremy J. 1947- (Oxford Univ. Press, 2000)
Few problems in mathematics have had the status of those posed by David Hilbert in 1900. Mathematicians have made their reputations by solving some of them like Fermat's last theorem, but several remain unsolved including the Riemann Hypotheses, which has eluded all the great minds of this century. A hundred years later, this book takes a fresh look at the problems, the man who set them, and the reasons for their lasting impact on the mathematics of the twentieth century. In this book, the authors consider what makes this the pre-eminent collection of problems in mathematics, what they tell us about what drives mathematicians, and the nature of reputation, influence and power in the world of modern mathematics.
Keywords: Hilbert, David; Hilbert, David <1862-1943>; Hilbert, David <1862-1943> - Influence; Hilbert, David, 1862-1943 -- Influence; Hilbert, David, 1862-1943; Geschichte 1900-2000; Hypothesen; Mathématiciens - Allemagne - Biographies; Mathématiques - Philosophie - Histoire - 20e siècle; Wiskunde; Geschichte; Mathematik; Philosophie; Mathematics -- Philosophy -- History -- 20th century; Mathematics -- History -- 20th century; Mathematicians -- Germany -- Biography; Hilbertsche Probleme; Deutschland; Biografie